Laboratories of politics: There is bottom-up diffusion of policy attention in the American federal system - Garlick , Alex (Political Research Quarterly)
A persistent question in the study of American federalism is if the states actually serve as (3z(Blaboratories of democracy(3y (Bfor the country as a whole. I argue that political attention to policy areas can diffuse upwards, from state legislatures to Congress. National and state legislators share a party brand and can learn from policy debates in other levels. In particular, we should expect to see the diffusion of messaging legislation, or bills that were introduced without the intention of becoming law, after members of Congress observe their political effects in the states. Using an original dataset of introduced bills in all 50 state legislatures in 22 policy areas since 1991 drawn from LexisNexis, I show a positive association between changes in the number of state legislative bills introduced in 12 policy areas and the number of Congressional bills introduced in the next session, which is taken as evidence of (3z(Bbottom-up(3y (Bdiffusion. This relationship is more prevalent between Republican state legislators and members of Congress, within state delegations, and in issue areas where the interest group community lobbies before both the states and national government. To the extent that states are laboratories for the nation, they may be political laboratories.- Reproduced s
Keywords: State politics, Text as data, Policy, Legislation, Federalism